Increasing the corrosion resistance of turbine - Hlushkova, D. B.; Bahrov, V. A.; Hrinchenko, O. D.; Stepanyuk, A. I.; Hnatiuk, A. A.; Kalinina, N. E.; Глушкова, Д. Б.; Багров, В. А.; Степанюк, А. І.; Гнатюк, А. А.; Гринченко, О. Д.; Калініна, Н. Є. (Харківський національний автомобільно-дорожній університет, 2021)
The reliability of the vane apparatus of steam turbines largely determines the operation of the turbine as a whole. The results of scientific research indicate that the surface operation of the blades in the wet - steam flow is caused by a combination of corrosion and drip erosion. The presence of chemical elements and compounds in the working fluid intensifies the process of blade wear. The pH value of the working environment, which can fluctuate significantly during operation, has a significant effect on the wear characteristics. The influence of methods of strengthening the leading edges of steam turbine blades made of steel is analyzed 15Х11МФ on corrosion resistance. Corrosion tests of blade samples were carried out, the inlet edges of which were strengthened in three ways: high current amplification, electrospark alloying with T15K6 alloy, electrospark alloying with steel 15Х11МФ According to the results of the tests, the layer strengthened by hardening by high-frequency currents has the lowest corrosion rate, the layer strengthened by electrospark alloying with T15K6 hard alloy has the highest. The corrosion rate of the layer reinforced by electrospark alloying of steel 15H11MF is 2.1 less than that of the layer reinforced with T15K6 alloy.
Підвищення корозійної стійкості лопаток турбін
Keywords: turbine blades; corrosion; erosion; electrospark alloying; hardened layer; лопатки турбін; корозія; ерозія; електроіскрове легування; зміцнений шар; 621.785; 10.30977/BUL.2219-5548.2021.94.0.91